- A can finish work in X days.

B can finish work in Y days.

Both can finish in **Z days = (X*Y) / (X+Y).**
- Both A and B together can do work in T days.

A can do this work in X days.

then, B can do it in **Y days = (X*T) / (X-T)**
- A can finish work in X days.

B can finish work in Y days.

C can finish work in Z days.

Together they can do work in **T days = (X*Y*Z)/ [(X*Y)+(Y*Z)+(X*Z)]**
- A can finish work in X days.

B can finish work in Y days.

**A*X = B*Y**

** Y = (A*X) / B**
- A can finish work in X days.

B can finish work in Y days.

A left work after P days then B need to work Q days

**Q = [(X – P) / X ] * Y**
- M1 person can do W1 work in D1 days and H1 hours

M2 person can do W2 work in D2 days and H2 hours

**M1D1H1 = M2D2H2**

### Like this:

Like Loading...

*Related*